Are high‐cost drug funding mechanisms fit for purpose? A retrospective study of individual funding requests in an NHS tertiary hospital. Issue 1 (12th July 2020) - Sanghvi, Sonali; Allen, Rachel; Cho, Steven; Ferner, Robin E.; Urquhart, Robert; Sofat, Reecha
Abstract : Aims: To report on a retrospective study of individual funding request (IFR) submissions from a large tertiary hospital and describe gaps in current mechanisms for funding of high‐cost medicines in England. Methods: Data on the number and outcome of IFR submissions submitted to commissioners between 2014/15 and 2018/19 was extracted from the electronic patient health record and a local high‐cost drug database. Results: In total, 230 IFRs were submitted: 112 to NHS England and 118 to a Clinical Commissioning Group (CCG). The decline rate for IFRs was 71% for NHS England and 34% for CCGs. Lack of exceptionality was the primary reason cited for declining IFRs submitted between 2016–18 ( n = 42/45; 93%). Half of the patients whose IFR was declined received treatment funded through other routes, the majority (13/23; 57%) from internal hospital budget. This was governed via a local high‐cost drug panel. Positive clinical outcomes were observed in 50% (4/8) of patients who received NHS England IFR‐funded treatment, 54% (19/35) who received CCG IFR‐funded treatment and 91% (21/23) who were funded via other routes. Conclusion: The high rate of IFR decline signals inefficient use of resource expended in the IFR process. Gaps in access to high‐cost medicines remain for patients with rare and refractory disease requiring urgent treatment, largely due to the demand for exceptionality from NHS commissioners. Local mechanisms address this unmet need but have limitations. An outcomes‐based evaluation approach to commissioning and greater transparency of previous funding decisions by commissioners may improve efficiency and equity in the IFR system.